2021
DOI: 10.1111/cod.13781
|View full text |Cite
|
Sign up to set email alerts
|

Changes in adhesive ingredients in continuous glucose monitoring systems may induce new contact allergy pattern

Abstract: Background: Medical devices (MD) in close skin-contact for a prolonged time, such as glucose monitoring (CGM) systems, are a risk factor for contact allergy, and there has been an increase in patients using these. Correct diagnosis demands targetted testing.Objectives: We report a new allergen in a continuous CGM system in which the adhesive was changed. The allergy pattern of the patients diagnosed is reported. Methods:The three patients reported were patch tested with an MD series, own material, and possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
5
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 24 publications
1
47
5
4
Order By: Relevance
“…72 Acrylates being in the adhesives (and also in the plastic material of the sensor housing) are known to induce skin reactions. 73,74 Short term studies with MI-GMs that use transcutaneous microneedles to sample ISF have demonstrated minor edema and erythema skin irritation that resolve without treatment. 75,76 The use of a powerful laser for NIO-GM measurements poses a risk of pronounced skin damage.…”
Section: Technological Challenges Across Platformsmentioning
confidence: 99%
“…72 Acrylates being in the adhesives (and also in the plastic material of the sensor housing) are known to induce skin reactions. 73,74 Short term studies with MI-GMs that use transcutaneous microneedles to sample ISF have demonstrated minor edema and erythema skin irritation that resolve without treatment. 75,76 The use of a powerful laser for NIO-GM measurements poses a risk of pronounced skin damage.…”
Section: Technological Challenges Across Platformsmentioning
confidence: 99%
“…7 2,2′-methylenebis(6-tert-butyl-4-methylphenol) monoacrylate, which is used as an ingredient in adhesive for some pumps, has also been implicated as a potential cause of contact allergy. 8…”
Section: Introductionmentioning
confidence: 99%
“…7 2,2′-methylenebis(6-tert-butyl-4-methylphenol) monoacrylate, which is used as an ingredient in adhesive for some pumps, has also been implicated as a potential cause of contact allergy. 8 There is a need for new ideas, new technologies, and new products for IISs. This three-part report characterizes (1) the patient burden associated with using current IISs, (2) new developments in extended wear technology, and (3) future directions for IIS developments that would be well received.…”
Section: Introductionmentioning
confidence: 99%
“…However, alterations in device content risk introducing new potential allergens, which in turn can cause even more contact allergies among users. 4 Isobornyl acrylate (IBOA) was the first main sensitizer in CGM systems, but by no means the last one. The allergen was identified and cases of CA confirmed in university clinics -without aid from the industry.…”
mentioning
confidence: 99%
“…5 Today, IBOA is just one of several allergens found in MD. 2,4,5,6 Unfortunately, it has been found in various MD from different manufacturers.…”
mentioning
confidence: 99%